Juvenile instars of Sellnickia caudata (Michael, 1908) (Acari, Oribatida, Sellnickiidae) - Ermilov, Sergey G.; Salavatulin, Vladimir M. (Zootaxa, 2024)
Juvenile instars of Sellnickia caudata (Michael, 1908) are described, based on specimens collected from tree branches and leaves of Dipterocarpus alatus in Vietnam.